Clinical Assessment of Stereoacuity and 3-D Stereoscopic Entertainment. (2nd October 2015) - Tidbury, Laurence P.; Black, Robert H.; O'Connor, Anna R.
Abstract: Background/Aims : The perception of compelling depth is often reported in individuals where no clinically measurable stereoacuity is apparent. We aim to investigate the potential cause of this finding by varying the amount of stereopsis available to the subject, and assessing their perception of depth viewing 3-D video clips and a Nintendo 3DS. Methods : Monocular blur was used to vary interocular VA difference, consequently creating 4 levels of measurable binocular deficit from normal stereoacuity to suppression. Stereoacuity was assessed at each level using the TNO, Preschool Randot®, Frisby, the FD2, and Distance Randot®. Subjects also completed an object depth identification task using the Nintendo 3DS, a static 3DTV stereoacuity test, and a 3-D perception rating task of 6 video clips. Results : As intraocular VA differences increased, stereoacuity of the 57 subjects (aged 16–62 years) decreased (eg, 110", 280", 340", and suppression). The ability to correctly identify depth on the Nintendo 3DS remained at 100% until suppression of one eye occurred. The perception of a compelling 3-D effect when viewing the video clips was rated high until suppression of one eye occurred, where the 3-D effect was still reported as fairly evident. Conclusion : If an individual has any level of measurable stereoacuity, the perception of 3-D when viewing stereoscopic entertainment is present. The presence of motion in stereoscopic video appears to provide cues to depth, where static cues are not sufficient. This suggests there is a need for a dynamic test of stereoacuity to be developed, to allow fully informed patient management decisions to be made.